A Small Horizontally Transferred Gene Cluster Contributes to the Sporulation of Alternaria alternata. (25th November 2019) - Wang, Mingshuang; Fu, Huilan; Ruan, Ruoxin
Abstract: Horizontal gene transfer (HGT) has been identified as an important source of genomic innovation in fungi. However, how HGT drove the evolution of Alternaria alternata, a necrotrophic fungus which can be ubiquitously isolated from soil and various plants and decaying plant materials is largely known. In this study, we identified 12 protein-encoding genes that are likely acquired from lineages outside Pezizomycotina. Phylogenetic trees and approximately unbiased comparative topology tests strongly supported the evolutionary origin of these genes. According to their predicted functions, these HGT candidates are involved in nitrogen and carbohydrate metabolism. Especially, five genes of them were likely transferred as a physically linked cluster from Tremellales (Basidiomycota). Functionally knocking out the five-gene cluster in an A. alternata isolate causing citrus brown spot resulted in an 80% decrease in asexual spore production in the deletion mutant. We further knocked out each of these five genes in this cluster and the resultant single-gene deletion mutants exhibited a various degree of reduction in spore production. Except for conidiation, functions of these genes associated with vegetative growth, stress tolerance, and virulence are very limited. Our results provide new evidence that HGT has played important roles over the course of the evolution of filamentous fungi.